ANTICIPATORY EFFORTS ON THE BEHAVIOR OF LGBT COMMUNITY IN INDONESIA: A Study of Anticipatory and Educational Roles of Religious Figures - muhibbuthabry muhibbuthabry; Sulaiman Sulaiman (Universitas Islam Negeri Ar-Raniry, 2019)
This present study concerned the roles of religious leaders towards LGBT prevention and LGBT behavior and the government policy towards LGBT prevention in North Sumatra and Aceh Provinces. The subjects of this study included religious leaders and local governments in Medan City, North Sumatra Province and Langsa City, Aceh Province. The study used qualitative methods with descriptive approaches. Data were collected using the purposive sampling technique. Study participants consisted of fifteen religious leaders and two related institutional leaders in Medan City and Langsa City. The result showed that the educational roles of religious leaders in preventing the LGBT behaviors included disseminating the risk of LGBT behavior, providing guidance, being educators, showing community roles, and being role models. In addition, the number of LGBT cases in Medan reached 600 cases while there was no case found yet in Langsa. In an effort to prevent the spread of LGBT, the local governments have employed preventive and curative measures although the curative measure has yet to properly implement due to the absence of LGBT law.